Exchange Rate and the Price Level in Socialist Economies. (IMF Working Papers; Working Paper, 1990)
The paper examines how the evolution from a classical centrally planned economy to a more market-oriented system will enhance the linkage between the exchange rate and the domestic price level. However, during the transition--as the economy continues to be predominantly state-owned, the inherited production structure is only gradually modified, capital and labor mobility are still relatively low and financial discipline is less-than-complete--the elasticity of the domestic price level with respect to a change in the exchange rate, or, to a change in world market prices, may still be lower than in an otherwise comparable market economy.